Convergent evolution of tRNA gene targeting preferences in compact genomes. Issue 1 (December 2016) - Spaller, Thomas; Kling, Eva; Glöckner, Gernot; Hillmann, Falk; Winckler, Thomas
Abstract Background In gene-dense genomes, mobile elements are confronted with highly selective pressure to amplify without causing excessive damage to the host. The targeting of tRNA genes as potentially safe integration sites has been developed by retrotransposons in various organisms such as the social amoebaDictyostelium discoideum and the yeastSaccharomyces cerevisiae . InD. discoideum, tRNA gene-targeting retrotransposons have expanded to approximately 3 % of the genome. Recently obtained genome sequences of species representing the evolutionary history of social amoebae enabled us to determine whether the targeting of tRNA genes is a generally successful strategy for mobile elements to colonize compact genomes. Results During the evolution of dictyostelids, different retrotransposon types independently developed the targeting of tRNA genes at least six times. DGLT-A elements are long terminal repeat (LTR) retrotransposons that display integration preferences ~15 bp upstream of tRNA gene-coding regions reminiscent of the yeast Ty3 element. Skipper elements are chromoviruses that have developed two subgroups: one has canonical chromo domains that may favor integration in centromeric regions, whereas the other has diverged chromo domains and is found ~100 bp downstream of tRNA genes. The integration ofD. discoideum non-LTR retrotransposons ~50 bp upstream (TRE5 elements) and ~100 bp downstream (TRE3 elements) of tRNA genes, respectively, likely emerged at the root of dictyostelid evolution. We identified two novel non-LTR retrotransposons unrelated to TREs: one with a TRE5-like integration behavior and the other with preference ~4 bp upstream of tRNA genes. Conclusions Dictyostelid retrotransposons demonstrate convergent evolution of tRNA gene targeting as a probable means to colonize the compact genomes of their hosts without being excessively mutagenic. However, high copy numbers of tRNA gene-associated retrotransposons, such as those observed inD. discoideum, are an exception, suggesting that the targeting of tRNA genes does not necessarily favor the amplification of position-specific integrating elements to high copy numbers under the repressive conditions that prevail in most host cells.